Third time lucky? An exploration of Hutchison Whampoa's involvement in the mobile telecommunications industry - Jason Whalley; Peter Curwen (International Telecommunications Society (ITS), 2011)
Each year the United Nations Conference on Trade and Development produces a report on foreign direct investment (FDI). This report highlights trends on FDI, and identifies the world's largest transnational corporation (TNC). Prominent among the largest TNS are telecommunication companies such as Vodafone and Telefónica. Less obvious due to its diversified description is Hutchison Whampoa, a large conglomerate with a long history of an active presence in the telecommunications industry. This paper charts the history of this involvement before focusing on whether its recent investment in third-generation (3G) licences will be as successful as previous its ones. Through analysing the 3G investments that it has made, this paper argues that Hutchison Whampoa is unlikely to enjoy the same success with these 3G investments as it has in the past with Orange and its Indian operations.
Keywords: L22; L96; M13; O33; 330; Hutchison Whampoa; 3 Group; operational performance; telecommunications